Реалізація адвокатом адміністративної процесуальної правосуб’єктності як суб’єктом надання безоплатної вторинної правової допомоги в адміністративному судочинстві - Шатрава, С. О.; Shatrava, S. O.; Джафарова, О. В.; Dzhafarova, O. V.; Горбачов, О. В.; Horbachov, O. V.; Валко, П.; Valko, P.; Джафарова Олена В'ячеславівна; Сергій Шатрава (Юридичний науковий електронний журнал. - 2024. - № 5. - С. 368-371, 2024)
Виявлено особливості реалізації адміністративної процесуальної правосуб’єктності адвоката в межах адміністративного судочинства в Україні. Наголошено, що реалізація адміністративної процесуальної правосуб’єктності адвоката, залученого до системи надання безоплатної вторинної правової допомоги представляє з себе цілеспрямовані дії адвоката щодо набуття сукупності прав та обов’язків, необхідних для участі в системі безоплатної вторинної правової допомоги, а також їх подальшого застосування в ході професійної, законодавчо регламентованої діяльності. Сутність професійної правничої допомоги здійснюваної адвокатом залученим до надання безоплатної вторинної правової допомоги при цьому не змінюється та залишається спрямованою на сприяння забезпеченню прав, свобод та законних інтересів фізичних осіб. Реалізацію правосуб’єктності адвокатів задіяних у системи БВПД умовно класифіковано на декілька окремих етапів: 1) етап допуску (або залучення) адвоката до участі у наданні безоплатної вторинної правової допомоги, який включає в себе 1.1) набуття адвокатом права здійснювати правничу допомогу у межах системи БВПД та 1.2) процедуру безпосереднього розподілу доручень на здійснення БВПД; 2) безпосередню реалізацію адміністративної процесуальної дієздатності адвоката в системі надання БВПД; 3) припинення діяльності адвоката з надання правничих послуг в системі безоплатної вторинної правової допомоги. Особливість правосуб’єктності адвоката БВПД полягає у поширенні її окрім адміністративного судочинства ще на декілька галузей права (кримінального, цивільного тощо). При цьому, процедура безпосереднього розподілу доручень на здійснення БВПД, відповідно до чинного судового рішення, в повному об’ємі реалізується лише в галузі цивільно-правових відносин, при чому деякі компоненти механізму її реалізації недостатньо прозорі. Додатково слід відзначити, що під час реалізації правосуб’єктності адвоката суб’єкта системи БВПД в ній не виявлено ознак спеціальної правосуб’єктності.

The study is focused on the administrative procedural role of the lawyer within the system of providing free secondary legal aid in Ukraine. The purpose of the study is to identify the peculiarities of the realization of the administrative procedural legal personality of the lawyer within the administrative proceedings in Ukraine. It is emphasized that the implementation of the administrative procedural legal personality of a lawyer involved in the system of providing free secondary legal aid is the purposeful actions of a lawyer to acquire a set of rights and obligations necessary for participation in the system of free secondary legal aid, as well as their further application in in the course of professional, legally regulated activities. At the same time, the essence of professional legal assistance provided by a lawyer involved in the provision of free secondary legal assistance does not change and remains aimed at helping to ensure the rights, freedoms and legitimate interests of individuals. The implementation of the legal personality of lawyers involved in the system of free secondary legal aid is conditionally classified into several separate stages: 1) the stage of admission (or involvement) of a lawyer to participate in the provision of free secondary legal aid, which includes 1.1) acquisition by a lawyer of the right to provide legal aid in within the framework of the system of free secondary legal aid and 1.2) the procedure for the direct distribution of orders for the implementation of free secondary legal aid; 2) direct implementation of the administrative procedural capacity of the lawyer in the system of providing free secondary legal assistance; 3) termination of the lawyer's activity in the provision of legal services in the system of free secondary legal aid. The peculiarity of the legal personality of a lawyer of free secondary legal assistance is that it is extended to several branches of law (criminal, civil, etc.) in addition to administrative proceedings. At the same time, the procedure of direct distribution of orders for the implementation of free secondary legal assistance, in accordance with the current court decision, is fully implemented only in the field of civil legal relations, while some components of the mechanism of its implementation are not transparent enough. In addition, it should be noted that during the implementation of the legal personality of the lawyer of the subject of the system of free secondary legal assistance, no signs of special legal personality were found in it.

Выявлены особенности реализации административной процессуальной правосубъектности адвоката в пределах административного судопроизводства в Украине. Подчеркнуто, что реализация административной процессуальной правосубъектности адвоката, вовлеченного в систему предоставления безвозмездной вторичной правовой помощи представляет собой целенаправленные действия адвоката по приобретению совокупности прав и обязанностей, необходимых для участия в системе безвозмездной вторичной правовой помощи, а также их дальнейшего применения в ходе профессиональной, законодательно регламентированной деятельности. Сущность профессиональной юридической помощи, осуществляемой адвокатом привлеченным к оказанию безвозмездной вторичной правовой помощи, при этом не меняется и остается направленной на содействие обеспечению прав, свобод и законных интересов физических лиц.
Implementation by a lawyer of administrative procedural legal personality as a subject of providing free secondary legal assistance in administrative proceedings
Keywords: адміністративне судочинство; адміністративний процес; інститут адвокатури; адвокатура; адвокат; правосуб’єктність; правоздатність; дієздатність; безоплатна правова допомога; безоплатна вторинна правова допомога; administrative proceedings; administrative process; institute of advocacy; advocacy; lawyer; legal personality; legal capacity; free legal aid; free secondary legal aid; административное судопроизводство; административный процесс; институт адвокатуры; правосубъектность; правоспособность; дееспособность; безвозмездная правовая помощь; безвозмездная вторичная правовая помощь